Response after Infection-Associated Rise in Clozapine Levels in Treatment-Resistant Schizoaffective Disorder - Nina H. Grootendorst-van Mil; Anna R. M. Huiskens; Sieds Dieleman; Tom K. Birkenhäger (Case Reports in Psychiatry)
The clinical management of patients with treatment-resistant psychotic disorders is still challenging despite years of extensive research. If first-line antipsychotic treatment proves ineffective, clozapine is considered golden standard. Herein, we report on a patient with schizoaffective disorder that initially showed no response to treatment with clozapine and ECT and therefore reached a therapeutic dead end. After an unintentional exposure to supratherapeutic clozapine levels, related to a pneumonia, a significant and persistent reduction of psychotic symptoms occurred. The report suggests a careful reevaluation of the clozapine dose in cases of treatment-resistant psychotic disorders with failed trials of clozapine. Further increase of dose may prove efficacious, although side effects should be closely monitored. Research to determine the upper threshold of clozapine for antipsychotic efficacy is warranted.